Karakteristik sifat fisikokimia madu hutan, madu budidaya, dan madu lebah tanpa sengat di Indonesia - Devi Fatmawati; Dede Robiatul Adawiyah; Uswatun Hasanah (AGROINTEK, 2026)
Indonesia is a vast archipelago with significant biodiversity, including honey bee species that produce large amounts of honey. Therefore, understanding the chemical and physical properties of the various types of honey produced is essential for improving the utilization and diversification of the national food supply. This study used a Completely Randomized Design (CRD) method with various types of Indonesian honey, namely forest honey, cultivated honey, and stingless bee honey obtained from Kalimantan, Sumatra, and Java. It included chemical characterization (moisture content, ash, pH, total phenolics, vitamin C, total sugar) and physical characterization (color and rheology) of honey. The result showed that cultivated honey has the best chemical properties (moisture content and total sugar). Forest honey has the highest vitamin C content. Honey from the stingless bee (Heterotrigona itama) from East Java has the lowest ash content and pH. The honey of the stingless bee Tetragonula leaviceps had the highest total phenol content. The physical properties of all honey were dominantly brownish-yellow and had a non-Newtonian dilatant flow behavior. The PCA results revealed that the chemical and physical properties of the honey samples differed significantly. There was a positive correlation between the total sugar and the constant viscosity index value of the honey.